Revolusi Hijau Merubah Sosial-Ekonomi Masyarakat Petani - Gultom, Ferdi; Harianto, Sugeng (TEMALI : Jurnal Pembangunan Sosial, 2021)
The green revolution is modernization in agriculture. In Indonesia, the green revolution is a government effort to increase economic development and food security. The program implemented since the New Order regime has shifted traditional agriculture to modern agriculture. This makes agriculture no longer based on ecological principles. In the end, the green revolution created dependence that ended in poverty. This article aims to explain the phenomenon of dependency of the farming community in Indonesia. This research uses the literature study research method, where data is obtained through books, journals, news, articles, and other relevant sources. The data were then analyzed and linked to the dependency theory. The results of this study found that the farming community in Indonesia is very dependent on chemical fertilizers. Chemical fertilizers are government-subsidized fertilizers, even though chemical fertilizers can damage the ecosystem. In addition, the scarcity of subsidized fertilizers makes farmers have to buy expensive non-subsidized fertilizers. Therefore, farmers are always in the poor group, thus creating social inequality. In the end, peasants depend on the compassion of their relatives, relatives, peasants, neighbors to survive in the life of the peasants, relatives, fellow farmers, and patrons (landlords and middlemen) just for a day's meal. They often have to give up to make savings, to borrow from rich people or financial institutions such as banks and cooperatives.